Potassium dose and nutritional diagnosis of virus-free garlic - Paviani, Angela Cristina; Feltrim, Anderson Luiz; Wamser, Anderson Fernando; Rozane, Danilo Eduardo; Wolschick, Neuro Hilton; Hahn, Leandro (Comunicata Scientiae, 2024)
Potassium (K) fertilizer application in garlic (Allium sativum L) is commonly based on current cultivars that are normally infected with phytopathogenic viruses. Garlic are being developed using meristem culture, but methods for K diagnosis in this type of garlic need to be validated. The objective was to evaluate methods for diagnosing nutritional status of virus-free garlic as a result of K doses through use of a specific K+ meter in soil solution and foliar sap, and to determine foliar K content and its relationship with yield and quality of bulbs. Treatments consisted of K2O doses: 0, 50, 100, 250 or 500 kg ha-1 established in 5 separate locations. In all locations, K2O was applied in a single dose, before planting and incorporated in the 0-0.2 m layer. Response of garlic to K fertilization was low, with marketable yield being significant at a single location, with the highest marketable yield associated with 309 kg ha-1 of K2O. The K content of the soil solution and the K in the foliar sap increased with application of increasing K dose. Due to the low response of marketable yield of garlic to K fertilization, technologies of nutritional diagnosis of K was not efficient. Therefore, future studies should focus on different soil K concentrations to validate the sensibility of these technologies.